Multifunctional vesicular coacervates as engineered supramolecular solvents for wastewater treatment. (May 2019) - Ballesteros-Gómez, Ana; Caballero-Casero, Noelia; García-Fonseca, Sergio; Lunar, Loreto; Rubio, Soledad
Abstract: In this study, multifunctional supramolecular solvents (SUPRASs) able to simultaneously extract ionic, polar and hydrophobic organic compounds from wastewater have been developed. SUPRASs were synthesized in aqueous solutions containing mixtures of carboxylic acids and carboxylates that underwent spontaneous self-assembly and coacervation under the addition of tetraalkylammonium ions. These SUPRAS consisted of coacervate droplets made up of large unilamellar vesicular aggregates bridged by tetraalkylammonium ions. Both, the high kinetic stability of vesicles and their strong interaction with tetraalkylammonium ions through different bonds working cooperatively, made supramolecular nanostructures in the SUPRAS chemically stable, which minimized the presence of solvent residues in the treated water. The suitability of the synthesized SUPRASs to behave as multifunctional extractants in water treatment was investigated by their application to the removal of anionic, cationic and ionizable dyes and PAHs. All the variables affecting the extraction process were optimized (i.e. chain length of the tetraalkylammonium ion, fractional SUPRAS phase volume, pH, ionic strength, pollutant concentration and stirring time/rate). All the pollutants selected were efficiently removed at room temperature and a fractional SUPRAS phase volume of 0.01. Applicability of the SUPRAS-based treatment to the efficient removal of dyes in textile effluents and benzo( a )pyrene in tap water was proved. Overall, the low cost, easy synthesis and high removal efficiency of these engineered SUPRASs make them highly promising for application in comprehensive wastewater treatments. Graphical abstract: Image 1 Highlights: Engineered supramolecular solvents are designed for water multipollutant removal. These green nanostructured liquids are synthesized by self-assembly of amphiphiles. They offer multiple binding interactions and solubilization sites for pollutants. The supramolecular nanostructures are chemically and kinetically stable. Neutral, anionic and cationic compounds of wide polarity are efficiently removed.